2021
DOI: 10.1002/rmv.2260
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the risk of SARS‐CoV‐2 reinfection over time

Abstract: Summary Despite over 140 million SARS‐CoV‐2 infections worldwide since the beginning of the pandemic, relatively few confirmed cases of SARS‐CoV‐2 reinfection have been reported. While immunity from SARS‐CoV‐2 infection is probable, at least in the short term, few studies have quantified the reinfection risk. To our knowledge, this is the first systematic review to synthesise the evidence on the risk of SARS‐CoV‐2 reinfection over time. A standardised protocol was employed, based on Cochrane methodo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
51
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 80 publications
(68 citation statements)
references
References 21 publications
4
51
0
Order By: Relevance
“…health care workers) or with other study designs (e.g. solely based on antibodies with thus unclear infection date or missing control groups) that are all in line with the notion that natural immunity significantly protects against reinfections ( Abrokwa et al, 2021 ; Fabianova et al, 2021 ; Hall et al, 2021 ; Hanrath et al, 2021 ; Harvey et al, 2021 ; Iversen et al, 2021 ; Jeffery-Smith et al, 2021 ; Kojima et al, 2021 ; Leidi et al, 2021 ; Letizia et al, 2021 ; O Murchu et al, 2021 ; Rennert and McMahan, 2021 ).…”
Section: Efficacy and Duration Of Natural Immunity Against Reinfectionsmentioning
confidence: 73%
“…health care workers) or with other study designs (e.g. solely based on antibodies with thus unclear infection date or missing control groups) that are all in line with the notion that natural immunity significantly protects against reinfections ( Abrokwa et al, 2021 ; Fabianova et al, 2021 ; Hall et al, 2021 ; Hanrath et al, 2021 ; Harvey et al, 2021 ; Iversen et al, 2021 ; Jeffery-Smith et al, 2021 ; Kojima et al, 2021 ; Leidi et al, 2021 ; Letizia et al, 2021 ; O Murchu et al, 2021 ; Rennert and McMahan, 2021 ).…”
Section: Efficacy and Duration Of Natural Immunity Against Reinfectionsmentioning
confidence: 73%
“…In conclusion, despite immunosuppressive therapy, TX patients developed a robust immune response after SARS-CoV-2 infection, comparable to that observed in IC patients. The immune response persists until one year after SARS-CoV-2 infection, and it is likely that the immunological memory could persist for a long time and may protect both the IC and TX populations from SARS-CoV-2 secondary infections [34,35]. Future evaluation of the magnitude and persistence of the immune response elicited by SARS-CoV-2 vaccines in transplant recipients would provide essential information about immune protection from COVID-19 that could be achieved in this fragile population.…”
Section: Discussionmentioning
confidence: 99%
“…One of the salient features of omicron is its ability to cause reinfection. Studies before the emergence of omicron showed 0.1%-1% risk of reinfection and prior infection with SARS-CoV-2 to give more than 80% protection against reinfection [26]. Linear data analysis from South Africa showed that while reinfection rates did not go up during the beta and delta waves, they went up significantly during the omicron wave; the hazard ratio for reinfection vs. primary infection between 1st and 27th November was 2.39 as compared to wave 1 [18].…”
Section: Reinfection Abilitymentioning
confidence: 99%